2013
DOI: 10.1166/jnn.2013.7525
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nanoparticle Shape, Size, and Surface Functionalization on Cellular Uptake

Abstract: With the rapid development of biotechnology and nanomedicine, extensive research has focused on the investigations of delivering large-cargo molecules using nanoparticles through the cell membrane for disease diagnosis and treatment. Various inorganic and polymeric nanoparticles with optimized surface properties have been developed to carry these active cargo molecules such as organic molecules, oligonucleotides and proteins. Phagocytosis and pinocytosis have been suggested as the two major uptake mechanisms f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(108 citation statements)
references
References 0 publications
1
106
0
1
Order By: Relevance
“…SiNPs were internalized into cells via endocytosis. 33,39,40 The TEM observation, as shown in Figure 2A, provided evidence of uptake of SiNPs in L-02 and HepG2 cells, showing that SiNPs were mainly distributed in cytoplasm, lysosomes, and autophagic vacuoles. Then we observed that SiNPs decreased cell viability of L-02 and HepG2 cells in a dose-and time-dependent manner.…”
Section: Discussionmentioning
confidence: 97%
“…SiNPs were internalized into cells via endocytosis. 33,39,40 The TEM observation, as shown in Figure 2A, provided evidence of uptake of SiNPs in L-02 and HepG2 cells, showing that SiNPs were mainly distributed in cytoplasm, lysosomes, and autophagic vacuoles. Then we observed that SiNPs decreased cell viability of L-02 and HepG2 cells in a dose-and time-dependent manner.…”
Section: Discussionmentioning
confidence: 97%
“…66 A review of the literature revealed that nonspherical NPs show great promise as cancer drugdelivery vectors, such as filamentous, wormlike micelles, or needle-like morphologies. This may be explained with reference to facilitated adhesion of NPs on cell membranes and subsequent facilitated endocytosis.…”
Section: Impact Of Physicochemical Properties On Targeting Efficiencymentioning
confidence: 99%
“…It is known that, whereas the free drug enters cells by simple diffusion, drug-loaded NPs may provide a different cell entry mechanism such as endocytosis, pinocytosis, or phagocytosis, which is still under discussion. 48,49 It has been suggested that drug-loaded NPs are too large to pass through both the plasma and nuclear membranes. Thus, the presence of the drug within the cell nucleus must occur only once it has been released from inside the NPs.…”
Section: 31mentioning
confidence: 99%